How the Cervical Microbiota Contributes to Cervical Cancer Risk in Sub-Saharan Africa - Klein, Cameron; Kahesa, Crispin; Mwaiselage, Julius; West, John T.; Wood, Charles; Angeletti, Peter C. (Frontiers in Cellular and Infection Microbiology, 2020)
Despite ongoing efforts, sub-Saharan Africa faces a higher cervical cancer burden than anywhere else in the world. Besides HPV infection, definitive factors of cervical cancer are still unclear. Particular states of the cervicovaginal microbiota and viral infections are associated with increased cervical cancer risk. Notably, HIV infection, which is prevalent in sub-Saharan Africa, greatly increases risk of cervicovaginal dysbiosis and cervical cancer. To better understand and address cervical cancer in sub-Saharan Africa, a better knowledge of the regional cervicovaginal microbiome is required This review establishes current knowledge of HPV, HIV, cervicovaginal infections, and the cervicovaginal microbiota in sub-Saharan Africa. Because population statistics are not available for the region, estimates are derived from smaller cohort studies. Microbiota associated with cervical inflammation have been found to be especially prevalent in sub-Saharan Africa, and to associate with increased cervical cancer risk. In addition to high prevalence and diversity of HIV and HPV, intracellular bacterial infections such as Chlamydia, Gonorrhea, and Mycoplasma hominis are much more common than in regions with a low burden of cervical cancer. This suggests the prevalence of cervical cancer in sub-Saharan Africa may be partially attributed to increased cervical inflammation resulting from higher likelihood of cervical infection and/or microbial dysbiosis.